Incidence of tubercle of Zuckerkandl of the thyroid and it’s surgical relation with recurrent laryngeal nerve and the superior parathyroid gland - Puravankara, Lemin Mohan; Gopi, Ellikunnel Vithon (International Surgery Journal, 2021)
Background: This study was carried out with the objective to identify the tubercle of Zuckerkandl in patients undergoing thyroidectomy and to establish the relationship of TZN with the recurrent laryngeal nerve and superior parathyroid gland. Methods: 100 patients posted for thyroidectomy for various causes in Government medical college, Kozhikode for a period of 1 year between March 2014 and March 2015. 92 patients underwent total thyroidectomy, 4 patients underwent left hemithyroidectomy and 4 patients underwent right hemithyroidectomy. A total of 192 lobes i.e. 96 right lobes and 96 left lobes were studied. Results: Of the 100 patients studied TZN was identified in 63 (63%) patients. Of the 192 lobes studied, TZN was identified in 100 lobes (52.08%). This was 59 of 96 (61.40%) lobes on the right side and 41 of 96 (42.70%) lobes on the left side. Of the 92 Total Thyroidectomies, TZN was found bilaterally in 36 (39.10%) cases. RLN was identified ‘posteromedial’ in relation in 99 of the 100 (99%) TZNs studied and not visualized in relation to TZN in 1 (1%) case. The Superior Parathyroid was identified ‘superolateral’ in relation in 93 (93%), ‘lateral’ in 6 (6%) and ‘inferolateral’ in 1 (1%) of 100 TZNs studied. Conclusions: Zuckerkandl’s tubercle is a posterior extension of lateral lobes of the thyroid gland, maintains a constant relationship with the RLN and the superior parathyroid gland. It can be used as an anatomical landmark to assist in preservation of the RLN and the superior parathyroid gland during thyroid surgery.